Cow, Bull, Woman, Man (Relief on a Vessel from the End of the Fifth Millennium BC from the Western Black Sea Coast) - Georgieva, Petya (Archaeologia Lituana, 2022)
In the Varna Eneolithic necropolis three gold applications were found with shapes presenting cattle in profile. They have no clear sexual characteristics. These figures are usually interpreted as bulls. Images with analogous shapes occur rarely on ceramic vessels as well.This paper presents a vessel from the settlement mound Kozareva Mogila (Bulgaria). Two anthropomorphic and two zoomorphic figures are depicted on it. The images are schematic, modeled in relief along the entire middle part, arranged in a horizontal belt and alternating anthropomorphic and zoomorphic. The anthropomorphic ones are presented facing the observer, differing from each other only in that one has embossed female breasts. The zoomorphic ones are presented in profile. In shape they are very close to the gold cattle figures from Varna. Like the human figures, one has a clearly marked sex: a phallus in relief. This indicates that one depicts a bull and the other a cow, a rare example of simultaneous presentation of female and male anthropomorphic and zoomorphic images with clearly marked sex. This scene is a key to identifying the gender of the gold zoomorphic figures from the Varna necropolis, commonly called bulls.
Keywords: gender in prehistory; gold; Varna Eneolithic necropolis; late Eneolithic; prehistory of the Balkans